Can intensive early childhood intervention programs eliminate income-based cognitive and achievement gaps? - Greg J. Duncan; Aaron J. Sojourner (Institute for the Study of Labor (IZA), 2012)
How much of the income-based gaps in cognitive ability and academic achievement could be closed by a two-year, center-based early childhood education intervention? Data from the Infant Health and Development Program (IHDP), which randomly assigned treatment to low birth weight children from both higher- and low-income families between ages one and three, shows much larger impacts among low- than higher-income children. Projecting IHDP impacts to the U.S. population's IQ and achievement trajectories suggests that such a program offered to low-income children would essentially eliminate the income-based gap at age three and between a third and three-quarters of the age-five and age-eight gaps.
Keywords: I2; J24; I3; 330; human capital; skill formation; education; early childhood; government policy; Frühkindliche Bildung; Bildungsinvestition; Wirkungsanalyse; Kognition; Bildungsniveau; Schätzung; USA